The Innovative Spiral of Development of the Entrepreneurial Potential in the National Economy - V. Yu. Popov (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The aim of this publication is to formulate theoretical foundations of the movement patterns of innovative solutions in a unified system of their development, organization of industrial and end-use. The research result is the concept of an innovative economic development spiral. It covers market fundamentals implementing innovative solutions as designer – manufacturer – consumer. The innovative nature of the product significantly alters the classic formula of market self-regulation, which requires the introduction of relevant institutional changes. Comparative statistical analysis showed a strong correlation between growth rates of GDP and of the volume of innovative products sold in Ukraine. Ensuring the output of the national economy on a continuous spiral of innovation development requires a systematic approach to the implementation of the following interrelated components: improving the management of fundamental innovative research; the combination of the potential of research and development with industry; stimulation of introduction of innovative products at enterprises; promoting creation of conditions for the promotion of innovative products to the final consumption market. Mastering innovation culture at the state level means the willingness of the government to constant changes in the institutional environment of innovative enterprises. The essence of the issue for further research of the business potential of the national economy goes far beyond a single scientific specialization. Institutional changes relate not only to different levels of individual market players, but also to various types of activities.